In utroque profecerimus: How does Philosophical Sermo Become Eloquent? - Kučinskienė, Audronė (Literatūra, 2025)
In his rhetorical treatises, Cicero establishes a clear distinction between sermo and oratio (Or. 12–13, 63–64; De Or. II. 159). The former, among other meanings, refers to a philosophical discourse, whereas the latter refers to rhetorical speech. He treats sermo as a poorer sort of oration on the grounds of lacking a rhetorical value. According to Cicero, philosophical modus dicendi, on the one hand, lacks the power of contention and strife, which is necessary for court and forum disputes, and, on the other hand, is not suitable for public speaking. Instead, it is rather welcome in close circles, friendly gatherings, and dinner parties. However, in the preface to the First Book of De Officiis, Cicero asserts that his own philosophical works (sc. sermones) are worth reading no less than his orations, because both types of writing can help to enrich Latin. Even more strikingly, he adds that he succeeded in developing to perfection both genres (Off. I. 3). This claim stands in contrast with his earlier philosophical treatises in which Cicero stood on the defensive against his critics and felt it necessary to explain his motives in writing philosophy in Latin. So, the question is: How and when did this shift occur from defending and viewing sermo as an inferior form of discourse to evaluating and recommending it to readers? In this paper, I briefly examine the meanings and different usage of the terms sermo and oratio in Cicero’s treatises, secondly, I undertake to show a certain development or change in Cicero’s approach to his philosophical writings, and, finally, I shall give some insights into the question raised above.
Keywords: Cicero; Orator; De officiis; philosophical speech; sermo; oratio; oration